2013
DOI: 10.1037/a0029386
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on the effectiveness and tolerability of group-based exposure therapy for posttraumatic stress disorder: Preliminary self-report findings from 20 veterans.

Abstract: Although an extensive body of empirical literature supports the efficacy of individual exposure therapy for posttraumatic stress disorder (PTSD), there is substantial debate about the suitability of exposurebased techniques in group treatment settings. Whereas some clinicians and researchers have predicted that these techniques may vicariously traumatize patients, others have argued that the group setting may facilitate exposure work by offering opportunities for normalization and social support. Few studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…In addition to the review outlined above, several recent articles have examined new group exposure protocols (e.g., Castillo, C'de Baca, Qualls, & Bornovalova, 2012;Mott et al, 2013;Ready et al, 2008;Ready, Sylvers et al, 2012a;Sutherland et al, 2012). The majority of these studies Ready et al, 2008;Ready, Sylvers et al, 2012a;Sutherland et al, 2012) have relied on a similar manual (originally developed by Lorenz et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…In addition to the review outlined above, several recent articles have examined new group exposure protocols (e.g., Castillo, C'de Baca, Qualls, & Bornovalova, 2012;Mott et al, 2013;Ready et al, 2008;Ready, Sylvers et al, 2012a;Sutherland et al, 2012). The majority of these studies Ready et al, 2008;Ready, Sylvers et al, 2012a;Sutherland et al, 2012) have relied on a similar manual (originally developed by Lorenz et al, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…When the veterans expressed the potential benefits of GBET, a veteran stated, "I wanted to see how this would help me," while another said, "I had agreed to do this, and would not back out." The feedback supported the power of unity and that veterans were not only committed to themselves, or the GBET group but also in showing dedication and honesty staff members [2].…”
Section: ) Treatment Approach: Exposure Therapymentioning
confidence: 74%
“…Referring to these promising benefits, others are augmenting extended GBET model settings [4]. A different approach to understanding GBET stems from a recent study (Mott et al, 2013), of receiving 20 combat veterans' perspectives of self-reporting GBET experiences. The concern that supports this approach is due to the substantial debate regarding GBET settings.…”
Section: ) Treatment Approach: Exposure Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies have examined outcomes from exposure-based therapies for PTSD within PCTs throughout the VA. In a retrospective chart review study, Mott et al (2013) found that Iraq and Afghanistan Veteran status as well as a history of psychiatric inpatient hospitalizations were associated with dropping out of Evidence Based Psychotherapy (i.e. Prolonged Exposure and Cognitive Processing Therapy).…”
Section: The Tolerability Of Psychotherapies For Ptsdmentioning
confidence: 99%